From disciplinary dependence to equally rightful concomitance? Discourse on the sensitive relation between linguistics and didactis based on the example of German linguistics and German language didactics as a foreign language - Pieklarz-Thien, Magdalena (Glottodidactica, 2018)
The role of linguistics in language education has always been contested and has generated non-homogeneous opinions since the beginning of the existence of that discipline. This paper attempts to provide a broader examination of the interrelation between these two disciplines over the last few decades. Considerations are based on the example of German linguistics and the teaching of German as foreign language. It constitutes a contribution to the discourse on the identity and autonomy of language education as a science.